Aerobic and Anaerobic Methanotrophic Communities Associated with Methane Hydrates Exposed on the Seafloor: A High-Pressure Sampling and Stable Isotope-Incubation Experiment - Case, David H.; Ijiri, Akira; Morono, Yuki; Tavormina, Patricia; Orphan, Victoria J.; Inagaki, Fumio (Frontiers in Microbiology, 2017)
High-pressure (HP) environments represent the largest volumetric majority of habitable space for microorganisms on the planet, including the deep-sea and subsurface biosphere. However, the importance of pressure as an environmental variable affecting deep microbial life and their biogeochemical functions in carbon cycling still remains poorly understood. Here, we designed a new high-volume HP-sediment core sampler that is deployable on the payload of a remotely operated vehicle and can maintain in situ HP conditions throughout multi-month enrichment incubations including daily amendments with liquid media and gases and daily effluent sampling for geochemical or microbiological analysis. Using the HP core device, we incubated sediment and overlying water associated with methane hydrate-exposed on the seafloor of the Joetsu Knoll, Japan, at 10 MPa and 4˚C for 45 days in the laboratory. Diversity analyses based on 16S rRNA and methane-related functional genes, as well as carbon isotopic analysis of methane and bicarbonate, indicated the stimulation of both aerobic and anaerobic methanotrophy driven by members of the Methylococcales, and ANME, respectively: i.e., aerobic methanotrophy was observed upon addition of oxygen whereas anaerobic processes subsequently occurred after oxygen consumption. These laboratory-measured rates at 10 MPa were generally in agreement with previously reported rates of methane oxidation in other oceanographic locations.